Hernando Rojas, Margarita M. Orozco, Homero Gil de Zúñiga y Magdalena Wojcieszak (Eds.) Comunicación y Ciudadanía, Bogotá, Universidad Externado De Colombia, 2011 - Muñiz, Carlos (Revista Latinoamericana de Opinión Pública, 2012)
Resumen